Isorhynchophylline alleviates learning and memory impairments induced by aluminum chloride in mice - Hui-Qin Li; Siu-Po Ip; Guo-Qing Zheng; Yan-Fang Xian; Zhi-Xiu Lin (BMC, 2018)
Abstract Background To evaluate the effect of Isorhynchophylline (IRN) on the learning and memory impairments induced by aluminum chloride (AlCl3) in mice. Methods Fifty male Balb-c mice (4-month-old) were randomly divided into five groups: control, AlCl3 plus vehicle, AlCl3 plus IRN (20 mg/kg), AlCl3 plus IRN (40 mg/kg) and AlCl3 plus donepezil (5 mg/kg). Learning and memory impairments were induced in mice by subcutaneously injecting with AlCl3 (50 mg/kg) once a day for 8 consecutive weeks. At the same time, mice were intragastrically given vehicle or IRN (20 and 40 mg/kg) or donepezil (5 mg/kg) 30 min before each AlCl3 injection. The spatial learning and memory function was assessed using radial arm maze. After sacrificed, the parameters of oxidative stress and cholinergic system in the brain tissues were examined with ELISA kits. Moreover, the expression of nuclear factor kappa B (NF-κB) signaling pathway was analyzed with western blotting. Results The results showed that treatment with IRN could significantly ameliorate the cognitive deficits induced by AlCl3 in mice. In addition, treatment with IRN was found to reduce the level of malondialdehyde, enhance the activities of superoxide dismutases and catalase, increase the level of glutathione, and markedly inhibit the activity of acetylcholinesterase (AChE) in the brain tissues of the AlCl3-treated mice. Moreover, IRN significantly suppressed the phosphorylation of NF-κB p65 and IκBα in the brain tissues of AlCl3-treated mice. However, IRN did not show significant effect on the activity of butyrylcholinesterase. Conclusion Our findings demonstrated for the first time that IRN could alleviate learning and memory impairments induced by AlCl3 in mice. The neuroprotective effect of IRN against AlCl3-induced AD is probably mediated, at least in part, through inhibiting the AChE activity and reducing the oxidative damage of brain tissue via suppress the NF-κB signaling pathway. These results contributed to a better understanding of the in vivo anti-AD mechanism of IRN. It was concluded that IRN could protect the learning and memory function.